Cyprus : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2010)
The financial sector is mostly comprised of the banking sector, which largely provides insurance and asset management services. A large part of banking system assets relates to subsidiaries and branches of foreign banks. The banking sector poses risks by virtue of its size and concentration. The Cypriot banking system has weathered the crisis better than many other euro zone area countries. Significant headwinds for the overall banking system are expected, and the cooperative banks appear particularly vulnerable.